Crossing cultures : insights from master teachers - Boyacigiller, Nakiye Avdan, 1953-; Goodman, Richard Alan; Phillips, Margaret E., 1949- (Routledge, 2003)
Provides teachers and trainers with proven methods for developing coping strategies and problem solving skills in the cross-cultural arena.